Magnetic anisotropy and deep ultraviolet photoresponse characteristics in Ga2O3:Cr vermicular nanowire thin film nanostructure. Issue 17 (27th February 2015) - Guo, Daoyou; Wu, Zhenping; Li, Peigang; Wang, Qianjing; Lei, Ming; Li, Linghong; Tang, Weihua
<x xml:space="preserve">Abstract</x> The Ga2O3:Cr vermicular nanowire thin film nanostructure with a big ferromagnetic anisotropy and obvious deep ultraviolet photoresponse was obtained by PLD.